GUT BACTERIAL MICROBIOME OF HIV-INFECTED PEOPLE - Yu. V. Zakharova (Журнал микробиологии, эпидемиологии и иммунобиологии, 2018)
Data on the state of the microflora of HIV-infected people and its participation in the progression of the disease are presented. Mechanisms and markers of bacterial translocation through the intestinal mucosa into the bloodstream, their importance for HIV-infected people are described. Study of intestinal microbiome in different groups of HIV-status people controversial data on the phylogenetic diversity of the intestinal microflora are shown. However, in most studies in HIV-infected increase in the intestine of members of the genus Prevotella, reduction of the quantitative level of Bacteroides spp. increase in the proportion of Proteobacteria compared to the other members of the intestinal flora are noted. It is shown that Proteobacteria in HIV-infected patients are more metabolically active than HIV-negative individuals. Further studies of the intestinal microbiome in HIV-infection are presented.